HUBUNGAN POLA ASUH ORANG TUA DENGAN PENGGUNA GADGET PADA ANAK USIA SEKOLAH DASAR DI MASYARAKAT DUSUN MUARA SELATAN DESA CIMPU KECAMATAN SULI KABUPATEN LUWU - Helen Periselo; Adithama Asmal (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2021)
Parenting patterns are the habits of parents, fathers or mothers in leading, nurturing and guiding children in the family. nurturing in the sense of maintaining by caring for and educating him. parenting patterns are divided into 3, namely: democratic parenting, permissive and authoritarian. This study aims to determine the relationship between parenting and gadget users in children. The method used is a cross sectional design approach, which aims to determine the relationship between democratic, permissive and authoritarian parenting patterns with the use of gadgets in children. sampling by purposive sampling. The instrument collects data using a questionnaire. Data analysis was univariate and bivariate using chi-squared. Analysis of the data using the chi square test with a significance level of = (0.05). The results of data analysis of respondents with the chi square test found that there was a relationship between democratic parenting and the use of gadgets with a p value = 0.034, the relationship between Permissive parenting and the use of gadgets with a p value = 0.034 and from the results of this study there was no negative relationship between Authoritarian parenting with gadget users, because the results of the data obtained show there is a positive relationship between parenting styles other than authoritarian. It is suggested that it is necessary to pay attention to the parenting pattern of parents to children, namely democratic parenting so that children can get used to being disciplined with time, especially when using gadgets